Le professeur de l’Université de Vilna S. Revkovski (1807—1863) - Žemaitis, Z. (Lithuanian Mathematical Journal, 1963)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: З. Жемайтис. Профессор Вильнюсского университета З. Ревковский (1807—1893) Z. Žemaitis. Vilniaus senojo universiteto profesorius Z. Revkovskis (1807—1893)